A flexible job shop scheduling approach with operators for coal export terminals – A mature approach. (March 2020) - Burdett, Robert L.; Corry, Paul; Eustace, Colin; Smith, Simon
Highlights: A mature approach for scheduling and resourcing activities of coal export terminals is proposed. Blending, dual reclaiming, de-ballasting delays, and through loading are focussed upon. An improved meta-heuristic algorithm is introduced The meta-heuristic has improved resource chromosome and perturbation techniques for pre-emption handling. A comprehensive suite of test problems is solved to demonstrate the efficacy of the approach Abstract: This article presents an improved scheduling approach for optimising the activities of a coal export terminal (CET) and includes for the first time, new methodology for handling blending, concurrency, de-ballasting delays, dual reclaiming and through loading. The proposed methodology can be applied to bulk materials import and export terminals and other very complex scheduling scenarios whose activities require multiple resources to be present and operating. It is also adaptable to industries with similarly complex scheduling environments with concurrency requirements and pre-emption. This scheduling problem is highly intricate and is far more challenging than traditional problems. As such it has been necessary to develop an improved meta-heuristic algorithm, with additional resource assignment chromosome and improved perturbation operators for pre-emption handling and resource assignment. A comprehensive suite of test problems is solved to demonstrate the efficacy of our approach and the capability to solve scenarios with the aforementioned features.